Modernisasi Pendidikan Islam di Minangkabau: Studi tentang Interaksi dengan Pan-Islamisme (1909-1945) - Fahri Hidayat; Mujibur Rohman (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2024)
This article aims to analyze the influence of pan-Islamism on the modernization of Islamic education in Minangkabau during the National Movement period. This study fills a gap in previous research that has not integrally examined the relationship between the two, even though pan-Islamism is an important factor in the modernization of Islamic education in Indonesia. The writing of this article employs a historical research method encompassing four stages: heuristics, verification, interpretation, and historiography. This article concludes that the ideas of Pan-Islamism influenced the modernization of Islamic education in Minangkabau in three aspects: the modernization of Islamic educational thought through the publication of magazines and newspapers, the modernization of Islamic educational institutions by transforming Surau into madrasah, and the modernization of Islamic educational organizations through the establishment of Persatuan Tarbiyah Islamiyah (Perti), an organization engaged in Islamic education.